2008
DOI: 10.1158/1078-0432.ccr-07-1442
|View full text |Cite
|
Sign up to set email alerts
|

Use of Yeast-SecretedIn vivoBiotinylated Recombinant Antibodies (Biobodies) in Bead-Based ELISA

Abstract: Purpose: To measure circulating antigens, sandwich ELISA assays require two complementary affinity reagents. Mouse monoclonal antibodies (mAb) and polyclonal antibodies (pAb) are commonly used, but because their production is lengthy and costly, recombinant antibodies are emerging as an attractive alternative. Experimental Design: We developed a new class of recombinant antibodies called biobodies (Bb) and compared them to mAb for use in serodiagnosis. Bbs were secreted biotinylated in vivo by diploid yeast an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 27 publications
(38 reference statements)
0
36
0
Order By: Relevance
“…In two studies (Bandiera et al 2013, Scholler et al 1999, there was unclear risk of bias in patient selection, and two studies (Moraes 2012, Scholler et al 2008) showed a high risk of bias in patient selection. One study (McIntosh et al 2004) showed high risk of bias in the index test and flow and timing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies (Bandiera et al 2013, Scholler et al 1999, there was unclear risk of bias in patient selection, and two studies (Moraes 2012, Scholler et al 2008) showed a high risk of bias in patient selection. One study (McIntosh et al 2004) showed high risk of bias in the index test and flow and timing.…”
Section: Resultsmentioning
confidence: 99%
“…One study (McIntosh et al 2004) showed high risk of bias in the index test and flow and timing. Three studies (McIntosh et al 2004, Moraes 2012, Scholler et al 2008) were classified as having a high risk of bias. The results of the quality assessment were presented in Figure 2 for the 12 included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Biobodies have been generated against HE4 95 and mesothelin 96 . We have also demonstrated that this technology can be used reliably in a highly-sensitive bead-based ELISA assay for screening large populations of women for ovarian cancer 5,67 and for serum biomarker discovery 6 . These novel approaches to biomarker discovery offers promise for improved ovarian cancer screening and for detection of recurrences.…”
Section: Biomarker Discovery For Ovarian Cancer Preventionmentioning
confidence: 96%
“…In addition to these efforts, we have generated a cost-and time-effective method for generating site-specific in vivo biotinylated recombinant antibodies secreted by yeast (Biobodies 5,95 ). Biobodies have been generated against HE4 95 and mesothelin 96 .…”
Section: Biomarker Discovery For Ovarian Cancer Preventionmentioning
confidence: 99%
“…A total of 18 studies (Scholler et al, 1999;Hellstrom et al, 2003;McIntosh et al, Scholler et al, 2008;Huhtinen et al, 2009;Montagnana et al, 2009;Shah et al, 2009;Abdel-Azeez et al, 2010;Nolen et al, 2010;Chang et al, 2011;Holcomb et al, 2011;Jacob et al, 2011;Van Gorp et al, 2011;Park et al, 2012) with 3865 patients who satisfied the inclusion criteria were analyzed. The results are shown in Table 1.…”
Section: Literature Search and Study Design Characteristicsmentioning
confidence: 99%